A multivariate long-memory model with structural breaks - Guglielmo Maria Caporale; Luis A. Gil-Alana (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper introduces a multivariate long-memory model with structural breaks. In the proposed framework, time series exhibit possibly fractional orders of integration which are allowed to be different in each subsample. The break date is endogenously determined using a procedure which minimises the residual sum of squares (RSS). Monte Carlo experiments show that this method for detecting breaks performs well in large samples. As an illustration, we estimate a trivariate VAR including prices, employment and GDP in both the US and Mexico. For the subsample preceding the break our findings are similar to those of earlier studies based on a standard VAR approach in both countries, in the sense that the variables exhibit integer degrees of integration. On the contrary, the series are found to be fractionally integrated after the break, with the fractional differencing parameters being higher than 1 in the case of Mexico.
Keywords: C22; 330; Zeitreihenanalyse; Multivariate Analyse; Strukturbruch; Theorie; Schätzung; Konjunktur; USA; Mexiko